PERSENTASE PENETASAN TELUR IKAN GABUS (Channa striata) PADA PH AIR YANG BERBEDA - ayu altiara; muslim .; mirna fitrani (Universitas Sriwijaya, 2016)
ABSTRACT The success in egg hatching is determined by internal and external factors. One of external factors is the acid level. The use of pH in egg hatching is to stimulate chorionase enzyme that can make chorion become soft. The purpose of this research is to determine the best pH value for hatching of snakehead eggs. This research had been conducted in Laboratorium Dasar Perikanan, Departement of Aquaculture, Agriculture Faculty, Sriwijaya University on January until February 2016. The research method used a completely randomized design with five treatments and three replications. The treatment were P1 (pH 5±0.2), P2 (pH 6±0.2), P3 (pH 7±0.2), P4 (pH 8±0.2) dan P5 (pH 9±0.2). The results showed that different values of water pH in snakehead hatching gave significant effect on hatching percentage, incubation time and survival rate of larvae but did not indicate significant effect on percentage of abnormal larvae. The highest hatching percentage was in treatment P5 (90.75%), the fastest incubation time was in treatment P4 (20.00 hours), the highest survival rate of larvae was in treatment P2 (85.31%) and the highest percentage of abnormal larvae was in treatment P1 (1.67%). During the research, water quality were in tolerance range for hatching and snakehead larvae rearing where DO (5.27-6.01 mg/l), ammonia (0.00-0.29 mg/l), and alkalinity (26-106 mg/l). Key words : Snakehead, Hatching, pH different